A case of botulism in the Czech Republic and current possibilities for detecting the neurotoxin produced by Clostridium botulinum - Dresler, Jiří; Matúšková, Kateřina; Kalaninová, Zuzana; Pompach, Petr; Volný, Michael; Novák, Petr; Burantová, Anna; Holub, Michal (Klinicka mikrobiologie a infekcni lekarstvi, 2023)
In the Czech Republic, botulism is a rare life-threatening disease. A total of 155 cases have been reported since 1960; according to the ISIN (formerly EPIDAT) database, there have been only three isolated cases since 2013, with the exception of a single occurrence of familial botulism in 2013. In our work, we present the occurrence of botulism after ingestion of pâté of untraceable origin by a couple who were hospitalized for botulotoxin food poisoning in July 2022. Their neurological symptoms were dominated by dysarthria. After administration of antibotulinum serum, their condition improved significantly. Patient samples were analyzed using affinity carriers and MALDI mass spectrometry, a modern highly sensitive technique for detecting the presence of botulinum neurotoxins. Unlike traditional detection by a difficult and costly biological experiment on mice, the above analysis does not require the killing of laboratory animals.
Keywords: myši; Clostridium botulinum; Czech Republic; botulismus; Botulism; Botulinum Toxins; neurotoxiny; zvířata; Česká republika; Animals; botulotoxiny; Neurotoxins; Mice